The Limits of Dispersal: Fine Scale Spatial Genetic Structure in Australian Sea Lions - Ahonen, Heidi; Lowther, Andrew D.; Harcourt, Robert G.; Goldsworthy, Simon D.; Charrier, Isabelle; Stow, Adam J. (Frontiers in Marine Science, 2016)
Describing patterns of connectivity throughout a species range is critical to conservation management. In common with other mammals, pinnipeds typically display male-biased dispersal. Earlier studies using mitochondrial DNA showed that the endangered Australian sea lion (Neophoca cinerea) exhibits extreme matrilineal structure throughout its range. If male dispersal were similarly restricted, most breeding colonies may not receive sufficient levels of new genetic variation to buffer against risks associated with inbreeding and environmental change. To address these concerns we used 16 microsatellite loci to obtain a more highly resolving measure of genetic structure among colonies and determine whether dispersal is male-biased. We found that both male and female Australian sea lions are highly philopatric with limited dispersal. Within those constraints, when animals disperse between close colonies (<110 km) there is a tendency for males to move further than females. Our findings are intriguing considering the dispersal potential of Australian sea lions and the unique asynchronous breeding opportunities that might be expected to provide an incentive for male reproductive movements between geographically close colonies.